FAKTOR PSIKOLOGIS SISWA/MAHASISWA DALAM PEMBELAJARAN BAHASA ASING: SEBUAH DILEMA BAGI PENGAJAR BAHASA INGGRIS - Widagdo, Arif (Jurnal Kreatif : Jurnal Kependidikan Dasar, 2020)
This paper aims at describing psychological factors in language acquisition and learning for students who learn second language acquisition. It found that external factors such as the characteristic of teacher, class and school condition had consistently no relation with the success of learning foreign language. On the other hand, student’s psychological conditions, as one of the internal factors, are potential to influence the foreign or second language acquisition. Psychological factor is a factor that is mentally or spiritually concerned with the aspects in students’ acquisition. At least, four of many factors, such as anxiety, attitude, aptitude, and motivation influence the students’ process of language acquisition. However, to cope the psychological problems of learning second language, it is suggested that the five strategies for coping with language anxiety, among of them are preparation strategy, relaxation, positive thinking, peer, and labeled resignation. Therefore, in maximizing the result of second language acquisition, the five strategies as illustrated are important as an alternative solution.